2022
DOI: 10.1111/jfbc.14134
|View full text |Cite
|
Sign up to set email alerts
|

Malus toringoides (Rehd.) Hughes improves glucose and lipid metabolism and liver injury in high fructose‐induced mice

Abstract: Malus toringoides (Rehd.) Hughes, as a traditional medicinal and edible plant used in Tibet, China, is used to treat hypertension, hyperlipidemia, and liver diseases. In recent decades, excessive fructose intake with diet has greatly increased the occurrence of a series of metabolic diseases including obesity, insulin resistance, hypertension, and hyperlipidemia. The present study was designed to investigate the effects of an ethanol extract of M. toringoides (EMT) on glucose and lipid metabolism and liver inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Rat diets were provided by XIETONG.ORGANISM Co., Ltd. Some studies found that the ethanol extract of plenty of plants has the function of treating hepatic steatosis (Abbas, Boby, Lee, Hong, & Park, 2022;Quan et al, 2022), but there is a lack of research on the treatment of obesity and liver steatosis with ethanol extract of Arctium lappa L root. Samples of 5 and 100 mg/kg•bw/day of ethanol extract of Arctium lappa L were used as the low monitoring dose and high monitoring dose respectively for the experiment.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Rat diets were provided by XIETONG.ORGANISM Co., Ltd. Some studies found that the ethanol extract of plenty of plants has the function of treating hepatic steatosis (Abbas, Boby, Lee, Hong, & Park, 2022;Quan et al, 2022), but there is a lack of research on the treatment of obesity and liver steatosis with ethanol extract of Arctium lappa L root. Samples of 5 and 100 mg/kg•bw/day of ethanol extract of Arctium lappa L were used as the low monitoring dose and high monitoring dose respectively for the experiment.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Histological examination was assessed by using haematoxylin and eosin staining (Quan et al, 2022). After the mice were sacrificed by cervical dislocation, the brain tissues and liver tissues harvested.…”
Section: Histological Examinationmentioning
confidence: 99%